PENGARUH INFLASI, INVESTASI, DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBI (Al Dzahab, 2022)
Purpose: This study aims to determine how the influence of inflation, investment, and labor on economic growth in Jambi Province in 2011-2020. Design/methodology/approach: Data analysis was carried out descriptively quantitatively with multiple linear regression method. Secondary data were obtained from the Central Statistics Agency of Jambi Province and Bank Indonesia.Findings: The results of the study partially show that inflation does not have a negative effect on economic growth in Jambi Province. Meanwhile, investment has an insignificant positive effect and labor has a significant positive effect on economic growth in Jambi Province. Meanwhile, simultaneous testing shows that inflation, investment, and labor have a significant effect on economic growth in Jambi Province.Research implications: Based on the results of the study, it is known that although the inflation rate has no effect on economic growth, the government must still control and maintain the inflation rate. Economic growth must still be driven by growth, the workforce must be increased every period